Examining the Mediating-Moderating Role of Entrepreneurial Orientation and Digital Competence on Entrepreneurial Intention in Vocational Education - Triyono, Mochamad Bruri; Mutohhar, Farid; Kholifah, Nur; Nurtanto, Muhammad; Subakti, Hani; Prasetya, Kiftian Hady (Journal of Technical Education and Training, 2023)
Abstract: The importance of intention in producing graduates who are ready for entrepreneurship has not been addressed in-depth in vocational education (VE). The absence of an entrepreneurial orientation supported by digital competence has become the focus of the main problem. In addition, low social and psychological capital is a consequence of these problems. This study examines the determination of the role of social and psychological capital, and entrepreneurial orientation on entrepreneurial intentions. In addition, entrepreneurial orientation was tested for its role as a mediator and tested for the moderating effect of digital competence. This ex-post facto study was conducted involving 757 participants who were VE students. Data were collected through the Entrepreneurial Intention Scale questionnaire. SEM analysis was used to test the direct effect based on the path coefficient and the mediating and moderating effect based on the bootstrap results. Findings revealed that social and psychological capital, and entrepreneurial orientation play a significant role in entrepreneurial intentions. Entrepreneurial orientation plays a significant role in mediating the influence of social capital and psychological capital in determining intentions. Finally, digital competence can prove its moderating role significantly in its interaction with entrepreneurial orientation in determining intentions. These results indicate the importance of social and psychological capital, and entrepreneurial orientation as an important foundation for forming entrepreneurial intentions in vocational education students. On the other hand, digital competence is very important in strengthening entrepreneurial orientation to stimulate the growth of entrepreneurial intentions.